(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The mangrove ecosystem is one of the potential coastal ecosystems in Ambon Bay waters, most of which are in Inner Ambon Bay.Threats to the mangrove ecosystem in the waters of Ambon Bay are the activities that take place around it. Moreover, several rivers that empty into Ambon Bay cause the entry of debris/waste from land. Previous studies have shown that Pb and Cd have been detected in seawater in Ambon Bay waters, so it is considered important to conduct research on mangrove ecosystem sediments. The purpose of this study was to determine the concentration of heavy metals (Pb and Cd) in sediments in the mangrove ecosystem of Ambon Bay. The sampling points of the sediment in mangrove ecosystems were carried out using purposive sampling method. Sample analysis was carried out at the Environmental Productivity Laboratory of IPB using the Nitric Acid-Perchloric Acid Digestion method. The results showed that the concentration of heavy metal Plumbum (Pb) ranged from 18.25-35.98 mg/kg and Cadmium (Cd) 1.57-2.70 mg/kg. The results showed that the concentration of heavy metal Plumbum (Pb) ranged from 18.25-35.98 mg/kg and Cadmium (Cd) 1.57-2.70 mg/kg. Based on the results of the analysis, it can be said that, although Pb was found in fairly high concentrations, it had not yet exceeded the toxic threshold, while Cd had approached the toxic threshold. Overall, it can be concluded that the sediment has been contaminated with heavy metals Pb and Cd but has not affected the mangrove ecosystem, and is an indication that natural filtration occurs.